Daughter of Rome - Afshar, Tessa (Thorndike, Maine : Center Point Large Print, 2020)
"When the daughter of a prominent Roman general meets a disinherited Jewish immigrant, neither one can dream of Gods plan to transform them into the most influential couple of the early church. Nor can they anticipate the mountains that will threaten to bury them. Their courtship unwittingly shadowed by murder and betrayal, Priscilla and Aquila slowly work to build a community of believers, while their lives grow increasingly complicated thanks to a shaggy dog, a mysterious runaway, and a ruthless foe desperate for love. But when theyre banished from their home by a capricious emperor, they must join forces with an unusual rabbi named Paul and fight to turn treachery into redemption"--Provided by publisher.
Keywords: Rabbis -- Fiction; Church history -- Primitive and early church, ca. 30-600; Fiction; Large type books; Romance fiction; Historical fiction; Christian fiction